ANALISIS KEGAGALAN MATERIAL PIPA FERRULE NICKEL ALLOY N06025 PADA WASTE HEAT BOILER AKIBAT SUHU TINGGI BERDASARKAN PENGUJIAN : MIKROGRAFI DAN KEKERASAN - Sanjaya Okky Wijayanto; Athanasius Priharyoto Bayuseno (JURNAL TEKNIK MESIN, 2013)
Ferrule pipe with nickel alloy N06025 material based on ASTM B 166-04standart is cromium-nikel alloy. In operation condition  ferrule pipe receives heat from reforming gas with the temperature of 960° C continously, It causes structural alteration on ferrule pipe itself. This paper analyze material failure because of high temperature, based on micrograph and thickness hardness examination. Chemical result on EDX examination shows that the existance of white scale with the composition of Na and O2 as high as 38.76 wt%. and 30.16 wt%, respectively. The result of micrograph examination shows that the description of micro structure on ferrule pipe is highly different than normal micro structure. On failure ferrule pipe material shows original grain structutre has vanished dan replaced by transformation shape sekunder product. The result of hardness vickers shows that ferule pipe speciment has higher hardness vickers number if compared with hardness vickers number on nickel alloy N06025 standart of ASTM. Material failure that appears because of high temperature corrotion due to tempering process and rapid quenching because leaking of water steam from shell tube boiler.